Educação e tecnologias digitais no contexto das escolas públicas do estado de São Paulo: um estudo no campo CTS - Falcão, Patricia Mirella de Paulo (2019)
During the last decades, several studies point for a new Society shaped and framed through the optical of a digital culture. New devices emerge in a high speed, precluding the updating of the most adventurers. In front of this apparent digital society, new languages, symbols and signs receive several configurations. Because of it, the inclusion as the exclusion is present. For this new configuration of idealized society, the digital devices make a part of the everyday life as sensory extension of the human being. One of the problematics from the digital culture is the exacerbated spread of information, between real and true, and how to change them, once they digress and dominate the minds, especially of the youngers, about knowledge. Would the public school be included or excluded of this new device? In front of this, the present search aimed understanding how and if it happens, in the public-school group of São Paulo state, specifically in the elementary school, the teaching of subjects trough the digital technologies. The study showed as the general objective map, if the Science teaching should be effectively through the digital technologies. Besides the general objective, four specified objectives were created, like: analyze laws, provisional measures, decrees and other official documents of state bodies that legislate about education in Brazil, mainly the Federal Government, about the guidelines for the Science and technology teaching; catalogue schools to map and analyze which the researches, of infrastructure, human and economic are reserved for the process of the teaching through the digital technologies, confer and describe if in the elected institutions put or are putting some public program about incentive or broked teaching, as the teachers involved in the process, their abilities, knowledge and formations to teach their subjects, characterize what is the students vision about the learning through the digital technologies, and understand what they think about the broked process and about the subjects. Besides, what is the proportion that these technologies take in their lifes as confering their knowledges and abilities about them. Analyzing the search fulcrum, the methodologic triangulation was realized through the interview with three different groups: a. students of elementary school; b. teachers of public schools; c. manager- teacher that knows about the Federal Government jobs about digital technologies at school. So, qualitative and quantitative analyses were done during the purposed study. The analyses point that there is a strong speech that, for conception, treats the children and adolescents as native digitals in a slant of knowledge about digital technologies. But, these knowledges are in the most about games and social groups, besides entertainment things, so, it’s not real. About the teachers, the search shows they frequently confuse the meanings about the broking through digital technologies, and those that searches a broked process, what they do only, once that we conclude school is suboptimal about digital culture. Finishing, the study points there is a big abyss among what the Federal Government speaks, its actions and the effective inclusion of the public schools in digital culture. Besides important questions that involve the digital Technologies in a social and historic slant, that aren’t worked. We conclude the possibilities of field studies STS need to be discussed as a way for inclusion of the school technologies, since the basic education.